Relationship of Science Process Skills on Critical Thinking Ability Review By Gender In Madrasah Aliyah - Darmaji Darmaji; Astalini Astalini; Dwi Agus Kurniawan*; Agnes Aktapianti Br.Ginting (Jurnal Pendidikan Sains Indonesia, 2021)
Science process skills are very important to be mastered by students to help improve critical thinking skills. The purpose of this study was to determine whether there is a relationship between science process skills and critical thinking skills in terms of gender. This type of research used is an experiment with a quantitative research approach. The sampling technique in this study was a simple random sampling technique with a sample size of 50 students. The instruments used in this study were observation sheets of science process skills and critical thinking skills test questions. The data analysis technique used is descriptive statistical analysis and inferential statistics. Based on the results of the correlation test that has been carried out, the Pearson correlation value is 0.648, which means that there is a strong relationship between science process skills and students' thinking skills. This research can be used as a guideline for scientific process skills research on critical thinking skills in the future. The update in this research is the relationship between science process skills and critical thinking skills based on gender